Pengaruh rasio diameter terhadap parameter-parameter energi turbin arus laut horizontal - Rumaherang, Wulfilla Maxmilian (Universitas Mataram, 2020)
The ducted tidal turbine models have been developed to utilize convertion of the kinetic energy on ocean currents. The research on refining the turbine characteristics has been carried out by modifying the turbine’s shape and size. The study of the duct diameter ratio effect on the energy characteristics of the turbine was done in this work. This study was conducted by modifying the duct diameter ratio () with the constant inlet diameter D0 and outlet D2. The flow conditions are analyzed for five cases of turbines with different shapes and diameters to determine the optimum conditions. The optimum value of the diameter ratio could be obtained at the maximum value of power coefficient CP. Flow velocity in the ducted turbine was measured at three turbine sections, namely; the inlet section, the impeller housing section, and the outlet section. The measurement of flow in turbines was carried out at the free stream velocity U0 = 1,5 m/s. The power coefficient CP and thrust coefficient CT were calculated based on flow velocity data on the turbine cVennell sections for each case. The power coefficient CP reaches the maximum value (Betz limit) at the resistance coefficient K = 2 and the value of axial induction factor a = 0,37. These values were founded at diameter ratio d=0,66. The value of thrust coefficient CT reaches the maximum value at K = 3,9, a = 0,53 and . The optimum value of the diameter ratio was founded at d=0,69.